Goodbye summer, hello autumn ebook - Pak, Kenard (Kenard Pak's Changing Seasons., 2016)
As trees sway in the cool breeze, blue jays head south, and leaves change their colors, everyone knows—autumn is on its way! Join a young girl as she takes a walk through forest and town, greeting all the signs of the coming season. In a series of conversations with every flower and creature and gust of wind, she says good-bye to summer and welcomes autumn.